Optimizing PBPU Satisfaction And PBPU Loyalty Through Competitive Advantages Supported By Marketing Strategies, PBPU Involvement And PBPU Trust In BPJS Health In West Java Province - Welly Surjono; Umi Narimawati (Prodi Manajemen S1 dan D3 Keuangan & Perbankan, 2022)
Health is a basic human need that will affect the quality of human life itself which in turn has an impact on the human development index of a country, therefore the Indonesian Government launched the National Health Insurance program by establishing an institution or agency that manages the National Health Insurance, namely BPJS Health. The government through BPJS Health has a target market of all Indonesian people to participate in the JKN program, so BPJS Health can provide satisfaction to participants and create participant loyalty through its competitive advantages compared to other similar insurances. Competitive advantage will be created through marketing strategies, PBPU involvement and PBPU's trust in this health insurance program.This study aims to provide more information about optimizing PBPU satisfaction and PBPU loyalty through competitive advantage supported by marketing strategies, PBPU involvement and PBPU trust.The research method used is descriptive with data collection using triangulation techniques. Keywords: PBPU, Satisfaction, Loyalty, Competitive Advantage, Marketing Strategy, Involvement, Trust.